MYC Binding Near Transcriptional End Sites Regulates Basal Gene Expression, Read‐Through Transcription, and Intragenic Contacts - Huabo Wang; Bingwei Ma; Taylor Stevens; Jessica Knapp; Jie Lu; Edward V. Prochownik (Advanced Science)
Abstract The MYC oncoprotein regulates numerous genes involved in processes such as cell cycle control and mitochondrial and ribosomal structure and function. This requires heterodimerization with its partner, MAX, and binding to specific promoter and enhancer elements. Here, it is shown that MYC and MAX also bind near transcriptional end sites (TESs) of over one‐sixth of all annotated genes. These interactions are dose‐dependent, evolutionarily conserved, stabilize the normally short‐lived MYC protein and regulate expression both in concert with and independent of MYC's binding elsewhere. MYC's TES‐associated binding, occurring in coordination with other transcription factors, alters the chromatin landscape, increases nuclease susceptibility and alters transcriptional read‐through, particularly in response to certain stresses. MYC‐bound TESs can directly contact promoters and appear to fine‐tune gene expression in response to both physiologic and pathologic stimuli. Collectively, these findings support a previously unrecognized role for MYC in regulating transcription and its read‐through via direct intragenic contacts between TESs and promoters.